Wirelessly powered large-area electronics for the Internet of Things - Portilla, Luis; Loganathan, Kalaivanan; Faber, Hendrik; Eid, Aline; Hester, Jimmy G. D; Tentzeris, Manos M; Fattori, Marco; Cantatore, Eugenio; Jiang, Chen; Nathan, Arokia; Fiori, Gianluca; Ibn-Mohammed, Taofeeq; et al. (Nature electronics, 2023)
Powering the increasing number of sensor nodes used in the Internet of Things creates a technological challenge. The economic and sustainability issues of battery-powered devices mean that wirelessly powered operation—combined with environmentally friendly circuit technologies—will be needed. Large-area electronics—which can be based on organic semiconductors, amorphous metal oxide semiconductors, semiconducting carbon nanotubes and two-dimensional semiconductors—could provide a solution. Here we examine the potential of large-area electronics technology in the development of sustainable, wirelessly powered Internet of Things sensor nodes. We provide a system-level analysis of wirelessly powered sensor nodes, identifying the constraints faced by such devices and highlighting promising architectures and design approaches. We then explore the use of large-area electronics technology in wirelessly powered Internet of Things sensor nodes, with a focus on low-power transistor circuits for digital processing and signal amplification, as well as high-speed diodes and printed antennas for data communication and radiofrequency energy harvesting.This Perspective explores the potential of large-area electronics in wirelessly powered sensor nodes for the Internet of Things, considering low-power circuits for digital processing and signal amplification, as well as diodes and printed antennas for data communication and radiofrequency energy harvesting.